NEWSPAPER COVERAGE OF THE CHIBOK GIRLS ABDUCTION IN NORTH-EAST NIGERIA - Helen O., Adekoya; Sarah, Ifidon; Patricia E., Chioma (IJRDO - Journal of Social Science and Humanities Research, 2016)
Since 2002 when the Boko Haram sect was first discovered in Nigeria, they has continued to distort the peace and safety of the country and create global concerns. The abduction of about 230 Chibok girls on April 14, 2014 and the fact that these girls are yet to be found still remains a mystery. As the watchdog of the society, the mass media is expected to bring forth such contemporary issues in their discourse, thereby setting the agenda, and keeping its diverse audiences abreast of the situation. Adopting the content analysis research design, this study comparatively investigated the level of coverage accorded to the discourse on the Chibok girls abduction buy two national dailies of: The Punch, and The Guardian. 30 news reports were sampled each from the papers. The findings revealed that both newspapers gave prominence to the Chibok girls abduction in their coverage. This proves that the media is living up to their role as the watchdog of the society given the existence of the coverage being analysed.